Knowledge and practice of breast self-examination among nursing and midwifery students in Ibadan, Nigeria (2014)
Background: Breast self-examination (BSE) is a check-up that a woman does by herself at home to look for changes or problems affecting the breast tissue. BSE is still recommended as a general approach to increasing breast health awareness and thus potentially allow for early detection of any anomalies because it is free, painless and easy to practice. This study assessed the knowledge and practice of BSE among Nursing and Midwifery students of School of Nursing and Midwifery, Eleyele Ibadan. Methods: The descriptive study was conducted with the use of structured questionnaires designed by the researchers. The internet resources and previous related studies served as the sources of content of the questionnaire. A simple random technique was used to select the participants for the study; the Nursing and Midwifery Council indexing record for the school being the sample frame. Thus, a total of 142 participants were recruited for the study. Results: The findings show that, majority (84.5%) of the respondents had good knowledge of BSE, while all of them had heard about BSE as at the time of data collection. However, over 90% had been practicing it prior to the period of data collection appropriately. Less than 15% of the respondents, had been able detect breast lumps while performing BSE. This category of the respondents claimed to have informed their parents before any action was taken. Conclusion: Breast cancer is the most severe and serious health problem faced by the public, majorly women. These nursing and midwifery students, most of whom were within the transitive phase from adolescent to adulthood have potential influence on one another, their immediate families and the society at large. This category of the nation’s population has been less studied in previous related researches. Therefore, educating them particularly during their professional training is very important